Comparison of uridine and N1-methylpseudouridine mRNA platforms in development of an Andes virus vaccine - Kuzmin, Ivan V.; Soto Acosta, Ruben; Pruitt, Layne; Wasdin, Perry T.; Kedarinath, Kritika; Hernandez, Keziah R.; Gonzales, Kristyn A.; Hill, Kharighan; Weidner, Nicole G.; Mire, Chad; Engdahl, Taylor B.; Moon, Woohyun J.; et al. (Nature communications, 2024)
The rodent-borne Andes virus (ANDV) causes a severe disease in humans. We developed an ANDV mRNA vaccine based on the M segment of the viral genome, either with regular uridine (U-mRNA) or N1-methylpseudouridine (m1Ψ-mRNA). Female mice immunized by m1Ψ-mRNA developed slightly greater germinal center (GC) responses than U-mRNA-immunized mice. Single cell RNA and BCR sequencing of the GC B cells revealed similar levels of activation, except an additional cluster of cells exhibiting interferon response in animals vaccinated with U-mRNA but not m1Ψ-mRNA. Similar immunoglobulin class-switching and somatic hypermutations were observed in response to the vaccines. Female Syrian hamsters were immunized via a prime–boost regimen with two doses of each vaccine. The titers of glycoprotein-binding antibodies were greater for U-mRNA construct than for m1Ψ-mRNA construct; however, the titers of ANDV-neutralizing antibodies were similar. Vaccinated animals were challenged with a lethal dose of ANDV, along with a naïve control group. All control animals and two animals vaccinated with a lower dose of m1Ψ-mRNA succumbed to infection whereas other vaccinated animals survived without evidence of virus replication. The data demonstrate the development of a protective vaccine against ANDV and the lack of a substantial effect of m1Ψ modification on immunogenicity and protection in rodents. Modified nucleosides are often used in mRNA vaccines and can affect protein expression and immunogenicity. Here, the authors compare M segment based Andes virus mRNA vaccines, either with regular uridine or N1-methylpseudouridine, and characterize immune response and protection in rodents.